2020
DOI: 10.18632/oncotarget.27682
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating tumor DNA in patients of operative colorectal and gastric cancers

Abstract: Liquid biopsy is a non-invasive tool to examine the genetic profile of tumors by identification of mutated circulating tumor DNA (ctDNA), which is often analyzed by next generation sequencing (NGS) or droplet digital PCR (ddPCR) assay. We first examined the ctDNA mutation in pre-operative plasma samples obtained from 154 colorectal cancer (CRC) and 46 gastric cancer (GC) patients, using the NGS-based panel assay. The overall detection rate of mutated ctDNA was 72.0% (144 of 200 patients), and the panel-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Other groups have similarly corroborated a low recurrence risk in ctDNA-negative patients for resected stage II–III CRC (2-year RFS rate of 89.4%) based on blood draws as early as 3–7 days postoperatively [ 26 ], whereas postoperative ctDNA-positivity has been associated with increased recurrence risk using tumor-informed assays in localized, resected CRC [ 23 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Detection Of Minimal Residual Disease and Recurrences In Resected Stage I–iii Colorectal Cancermentioning
confidence: 93%
“…Other groups have similarly corroborated a low recurrence risk in ctDNA-negative patients for resected stage II–III CRC (2-year RFS rate of 89.4%) based on blood draws as early as 3–7 days postoperatively [ 26 ], whereas postoperative ctDNA-positivity has been associated with increased recurrence risk using tumor-informed assays in localized, resected CRC [ 23 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Detection Of Minimal Residual Disease and Recurrences In Resected Stage I–iii Colorectal Cancermentioning
confidence: 93%
“…Indeed, partitioning DNA molecules through the generation of millions of droplets and the possible additivity of reactions reduce template competition and allows to reach a theoretical detection threshold of mutations until 1/100,000 [ 8 ]. Therefore, digital droplet PCR (ddPCR) might appear as the most sensitive, suitable and fast technology [ 7 , 9 , 10 , 11 ]. Several ddPCR platforms are now being commercialized but still contain a restricted number of probes in each run.…”
Section: Molecular Aspectsmentioning
confidence: 99%
“…Liquid biopsy-based post-operative assessments would be able to detect tumor relapse/recurrence a few to several months earlier than current radiological imaging modalities [ 101 , 108 , 109 , 110 ]. According to a recent study, patients with positive ctDNA after their surgery showed a significantly shorter recurrence-free survival than patients without ctDNA [ 111 ]. This implies that screening of ctDNA with liquid biopsy can be useful in identifying patients at high risk of post-operative recurrence, and that serial screening of ctDNA would allow early detection of tumor relapse/recurrence.…”
Section: Detection Of Minimal Residual Disease (Mrd) By Liquid Biopsy After the Curative Resectionmentioning
confidence: 99%